USE OF LANDOWNER AND RESIDENT OBSERVATIONS TO EVALUATE WILD TURKEY RELEASES - Steven E. Backs; Robin P. Bouta; Robert M. Platte (Wildlife Society Bulletin)
Abstract: Systematic interviews of landowners and residents were used to evaluate the status of wild turkey releases on 7 areas in Indiana. A total of 367 landowners/residents was interviewed during June and July 1983 and asked to record observations of wild turkeys made during the next year on postage‐paid postcards. By June 1984, a total of 426 observations was received from the interviews and observation cards returned. The average area around release sites covered by interviews was about 130 km2. About half (51%) of the initial contacts displayed a positive observation response. Reported brood sizes averaged 7.4 birds. Observations of marked birds averaged 22% the first year following release and decreased the following year suggesting either a stable or growing population. The overall average group size reported was 2.9 birds and were observed an average of 4.2 km from the release site. Utility and limitations of this technique are discussed. Approximately 1 man‐hour was expended per observation received and each observation represented approximately 3 birds. Gobbling count surveys, by comparison, required a minimum of 6‐7 man‐hours per bird heard. Public relation benefits of landowner/resident contacts to the restoration program are reviewed.